PENGEMBANGAN MODUL EDUKASI TUNJUK AJAR MELAYU TERHADAP MOTIVASI BELAJAR ANAK - Sari, Winda Prima; Saam, Zulfan; Umari, Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to develop a malay teachingpointing education module on children’s learning motivation.The reseach method used is research and development with reference to the R&D steps, namely : potentials and problems, data collection, product design, design validation, design revision and product manufacturing. The instrument used was the assessment scale sheet, which was validated by 4 materral expert, two lecturers and two bk teachers. The result of the research on the development of the malay teaching pointing education medule developed are in the good category and also valid with a score of 3.7 so this medule can be said to be valid for use and publication.Key Words: Education Module, Point to Tunjuk Ajar, Motivation to Learn